God's laboratory : assisted reproduction in the Andes - Roberts, Elizabeth F. S., 1970- (University of California Press, 2012)
Assisted reproduction, with its test tubes, injections, and gamete donors, often raises important concerns regarding matters of life and kinship. Yet these concerns do not take the same form everywhere around the world. In this innovative ethnography of in vitro fertilization in Ecuador, Elizabeth Roberts shows how having children through biotechnological intervention is not only tolerated, it is embraced by the population, despite widespread poverty and official condemnation by the Catholic Church. Roberts takes us into clinics, laboratories, and homes, providing a textured picture of the int.